POLA DAN KECENDERUNGAN STUDI KONFLIK DI INDONESIA : Analisis terhadap Studi Kekerasan pada Kasus Aceh dan Ambon - Ichwanuddin, Wawan (Pusat Penelitian Politik, 2011)
Post Soeharto Indonesia is not only characterized by a democratic transition but also the outbreak oflargescale violent conflicts in various regions Beyond the destruction ofproperty the wave ofconflict in many regionshas also claimed thousands of lives andforced more than 1 3 million others into refugees This phenomenon inspires the emergence ofinitiativesfrom various parties to engage directly seek conflict resolution and buildpeaceSome ofthem contribute through a series ofscientific studies to analyze the causes and alternative resolutions ofthe conflicts This article presents the results ofa review to conflict studies conducted in the case ofMaluku andAceh There are three issues that are thefocus ofanalysis in this article namely the causes ofviolence roles andrelationships between parties and the conflict resolutions